2022
DOI: 10.1186/s43163-022-00228-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging on dichotic listening ability

Abstract: Background Elderly patients frequently suffer from problems in speech discrimination especially in noisy situation, and they also have several problems from using amplifications devices especially binaural amplification. This necessitates the need for central auditory evaluation in association of peripheral auditory evaluation. The aim of the present study was to explore the effects of aging on dichotic listening performance. This was a case-control study conducted at the Audiology Unit, ENT De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…In comparison with similar studies, our findings align with the work of Andrade et al [1], Jerger et al [9], Tawfik and Shafik [16], Jerger and Martin [8], Jain et al [7], and Takio et al [15].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In comparison with similar studies, our findings align with the work of Andrade et al [1], Jerger et al [9], Tawfik and Shafik [16], Jerger and Martin [8], Jain et al [7], and Takio et al [15].…”
Section: Discussionsupporting
confidence: 93%
“…Like Andrade et al [1], we observed that there was a negative correlation between age and correct response scores in both ears, with the worst performance occurring in the older group. Similarly, in line with Jerger et al [9] and Tawfik and Shafik [16], our results indicate lower scores in the elderly group than in the younger group across various dichotic listening parameters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation